PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN SEREAL SARAPAN PAGI ENERGEN - Alfitriani Andharesti; Lia Nirawati (STKIP Persada Khatulistiwa Sintang, 2023)
Intense competition has led to competition between companies and led to the emergence of various similar companies that compete strictly in showing their existence. This study aims to determine the effect of Brand image and Product Quality on Customer Loyalty of Energen Breakfast Cereals Study at Surabaya State University. The type of research used is quantitative. The measurement scale used is the Likert scale. The population in this study were consumers who had bought and consumed Energen products. The sample used was 100 students at state universities in Surabaya. Primary data obtained directly by distributing questionnaires. Influence test using regression test with hypothesis testing using t test and F test. Based on the results of data processing it can be concluded that Brand image, Product Quality and Trust simultaneously have a significant effect on customer loyalty of energen breakfast cereals; Brand image partially has a positive and significant effect on Customer Loyalty of energen breakfast cereals; Product Quality partially has a positive and significant effect on Customer Loyalty of energen breakfast cereals; Trust partially has a positive and significant effect on Customer Loyalty of energen breakfast cereals